2022
DOI: 10.47268/pamali.v2i1.817
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm In Economy About Maqashid Al-Sharia Theory: Reformulation Of Ibn-Asyur

Abstract: Introduction: This article examines the theory of sharia maqasid based on the thoughts of Ibn Assyria. Maqasid sharia, as one of the most important concepts in the study of Islamic law, is a universal goal that will be achieved by sharia and realized in life. There is a large framework of sharia maqasid according to Ibn Assyria, namely the principle of Qashdi, the principle of responsibility, the principle of Istikhlaf and Fitrah, and the principle of equality. The objectives of sharia that ibn Assyria has set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…This moral and holistic approach ensures that animals are not only slaughtered humanely but also raised in environments that do not cause them unnecessary suffering. Moreover, shariah principles extend to the avoidance of wastefulness and the promotion of sustainability in food production, which is based on the concept of Maqasid Al-Sharia (Amin et al, 2023;Disemadi, Al-Fatih, & Yusro, 2020;Rofiq & Hasbi, 2022). The implementation of these principles is a reflection of the broader Islamic values of compassion, responsibility, and respect for all of Allah's creations, integrating ethical considerations into every stage of the food production and consumption process (Rofiq & Hasbi, 2022).…”
Section: Results and Discussion Halal Certification In Islamic And Na...mentioning
confidence: 99%
“…This moral and holistic approach ensures that animals are not only slaughtered humanely but also raised in environments that do not cause them unnecessary suffering. Moreover, shariah principles extend to the avoidance of wastefulness and the promotion of sustainability in food production, which is based on the concept of Maqasid Al-Sharia (Amin et al, 2023;Disemadi, Al-Fatih, & Yusro, 2020;Rofiq & Hasbi, 2022). The implementation of these principles is a reflection of the broader Islamic values of compassion, responsibility, and respect for all of Allah's creations, integrating ethical considerations into every stage of the food production and consumption process (Rofiq & Hasbi, 2022).…”
Section: Results and Discussion Halal Certification In Islamic And Na...mentioning
confidence: 99%
“…Thoughts about Maqashid Syariah can be divided into three stages, namely foundation, development, and contemporary (Al-Ayubi & Halawatuddu'a, 2021). Ibnu Assyria, who is one of the scholars who contributed to the development of Maqashid Syariah, established five criteria to recognize those categorized as maslahah and masadah (Rofiq & Hasbi, 2022). According to Al-Syatibi, Maqashid Syariah is divided into two things, namely legal establishment based on illat and al-mashalih wa al-mafasid based on three levels of benefit.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Maqashid Sharia is a universal goal that will be achieved by Sharia and realized in life. It is applied in various fields of the economy, including monetary policy, Islamic social finance, Islamic banking, and annual reports of Islamic commercial banks (Anisa et al, 2020;Soemitra et al, 2021;Al-Ayubi & Halawatuddu'a, 2021;Rofiq & Hasbi, 2022). In addition, the prohibition of usury is also one of the principles of Maqashid Syariah, which provides a perspective on the prohibition of usury (interest).…”
Section: Introductionmentioning
confidence: 99%
“…The stages of thinking about Maqashid Sharia can be organized into three phases, namely foundation, development, and contemporary (Al-Ayubi & Halawatuddu'a, 2021). Ibn Assyria, one of the scholars who played an important role in the development of Maqashid Sharia, established five criteria to recognize what can be categorized as maslahah and masadah (Rofiq & Hasbi, 2022). Al-Syatibi, in his view, divides Maqashid Sharia into two aspects, namely the establishment of law based on illat and al-mashalih wa al-mafasid based on three levels of benefit.…”
Section: The Concept Of Maqashid Sharia and Bankingmentioning
confidence: 99%
“…Yusup & Nasution (2020) revealed that the implementation of Maqashid Shariah in banking can be assessed through the Maqashid Shariah Index (MSI) method which has three main objectives, namely educating the public, upholding justice, and advancing the public interest. This approach aims to ensure that Islamic banking is based on sharia principles (Rofiq & Hasbi, 2022). This is reinforced by research from Ardila et al (2019) which explains that the MSI method can be used to measure the performance of Islamic banks based on sharia objectives, not just financial performance.…”
Section: The Concept Of Maqashid Sharia and Bankingmentioning
confidence: 99%